An assessment of gender sensitive adaptations options to climate change in smallholder areas of Zimbabwe, using climate analogue analysis and considering farmer perceptions - Musiyiwa K; Filho WL; Nyamangara, Justice; Harris D (Soil Science Society of East Africa, 2013)
Current projections suggest that the impacts of warmer climates on smallholder production by the middle of this century, are excpected to be mainly negative. Both the livelihoods and food security of smallholder households can be improved through suitable strategies for handling climate- induced risks and socio-economic and biophysical constraints. This paper describes the use of climate analogue areas together with an assessment of farmers´ perceptions, within the framework of the project CALESA. In particular, it considers them as tools for climate-risk analysis and assessment of adapation options. The importance for mainstreaming gender sensitive options for climate change planning and policy is also herewith illustrated. Climate analogues for 2050s were identified in smallholder areas of Zimbabwe based on 30 years metereological data. Pairs of sites with similar annual rainfall totals, which differed by 2-4 degrees Celsius in mean annual temperature (following the forecast effects of global warming for the 2050s) consist of Chiredzi which represent Matobo for drier areas, and Kadoma for wetter areas, which represent Mazowe/Goromonzi. Preliminary results for the 2010/2011 cropping season show different preferences for crop management strategies, particulalry between the dry analogue pair, with respect to crops choices as well as soil and water management strategies. In drier areas, implications are for increased uptake of small grains, in 2050s climates. For wetter climates, soil and water management stragegies are important options for smallholders. Gender issues for differently managed households seem to vary across sites. At drier sites, gender issues include labour for production and processing of the small grains, against a background of male labour migration. At wetter sites, access to draft power, labour, agricultural assets, social and financial capital in differently managed households are important for increasing adoption of effective crop management strategies.